Survey of clinical staff knowledge on the long‐term outcomes of very preterm infants delivered in a tertiary referral hospital. (26th April 2021) - Abdul Aziz, Safiyyah; Athalye‐Jape, Gayatri; Agrawal, Sachin; Sharp, Mary
Abstract : Aim: To assess knowledge of our neonatal intensive care unit clinical staff regarding preterm neurodevelopmental outcomes using the 33‐item Preterm Birth Knowledge Scale (PB‐KS). Methods: An anonymous convenience sampling survey of clinical staff in the Neonatal Directorate was conducted between July and December 2019. PB‐KS, demographic information and prior staff education on long‐term outcomes in very preterm infants were collected. Results: There were 56 responses (five neonatologists, eight paediatric trainees, 41 neonatal nurses and two allied health staff). Responses were scored as correct or incorrect. The mean score on the PB‐KS was 19.5 (range: 4–29 out of 40) with 50% correct answers. Accuracy was highest (96%) for rates of cerebral palsy and lowest (11%) for estimation of quality of life among preterm survivors. Staff reported training in long‐term outcomes of preterm infants through attending a conference/seminar (20%) or a combination of formal training and seminars (41.1%). Over half of our clinical staff reported a lack of formal training. Formally trained clinical staff scored significantly better in this survey. Didactic seminars were indicated as preferred choice for staff education. Conclusions: Results of our survey will assist in developing a customised educational programme to address identified gaps in the knowledge of clinical staff as our survey also showed significantly better scores among staff who were formally trained about long‐term outcomes in very preterm infants. Staff responses indicated that knowledge on long‐term outcomes was variable but more accurate with regard to more severe disabilities and shorter‐term developmental outcomes.